2009
DOI: 10.1177/0363546509350296
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Levels after Characterized Chondrocyte Implantation versus Microfracture in the Knee and the Relationship to Objective Functional Outcome with 2-year Follow-up

Abstract: Despite differences between the characterized chondrocyte implantation and microfracture procedures, patients' activity levels were comparable at 2 years after surgery. Lack of low-load activities after surgery adversely affected functional outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
34
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 41 publications
0
34
0
Order By: Relevance
“…42,60 Studies included in this review showed improved hop test performance over time after surgery. 68,69 However, deficits of greater than 15% in the involved limb (corresponding LSI, less than 85%) persisted in nearly one third of the study sample for up to 2 years postprocedure. …”
mentioning
confidence: 92%
See 4 more Smart Citations
“…42,60 Studies included in this review showed improved hop test performance over time after surgery. 68,69 However, deficits of greater than 15% in the involved limb (corresponding LSI, less than 85%) persisted in nearly one third of the study sample for up to 2 years postprocedure. …”
mentioning
confidence: 92%
“…40,47 Items with the highest average scores were for diagnostic certainty and outcome criteria (description of outcome measures, timing of assessment, and use of outcomes with good reliability and sensitivity). Items with lower average item scores were for type of study and procedure of outcome assessment.In terms of lesion location, 6 studies 19,24,39,40,47,59 included participants with lesions in the tibiofemoral (medial/ lateral femoral condyle, tibial plateau)With cartilage terms plus English language/humans filter (searches 1 and 2), n = 7326 Initial search (with variables of interest, searches 4, 5, 6, 7 and removed duplicates), n = 2612 • Outcomes related to muscle performance (search 4), n = 421 • Outcomes related to biomechanics/joint loading (search 5), n = 401 • Outcomes related to performance-based function (search 6), n = 1403 • Outcomes related to rehabilitation protocols (search 7), n = 387Excluded based on animal and cadaver studies (not found by filter), cartilage defects in other joints (not the knee), concomitant or additional surgeries performed with cartilage procedure, n = 762Excluded based on patient population of interest (eg, osteoarthritis, pediatric); outcome measures not related to performance-based measures (eg, patient-reported outcomes only); outcomes pertaining to histology, imaging, or surgery (eg, adverse events); or surgical-technique studies, n = 1834 and patellofemoral (patella, trochlea) compartments, and 10 studies [12][13][14][15][16][17][18]20,68,69 included only those with lesions in the tibiofemoral compartments (medial/ lateral condyle, tibial plateau). Of the 16 included studies, 3 evaluated outcomes following MF techniques 24,68,69 and 15 studies [12][13][14][15][16][17][18][19][20]39,40,…”
mentioning
confidence: 99%
See 3 more Smart Citations